2020
DOI: 10.3390/antibiotics9090546
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review on the Impact of Guidelines Adherence on Antibiotic Prescription in Respiratory Infections

Abstract: Overuse and inappropriate antibiotic prescription for respiratory tract infections (RTI) are one of the major contributors to the current antibiotic resistance problem. Guidelines provide support to prescribers for proper decision-making. Our purpose is to review the impact of prescribers’ exposure to guidelines in antibiotic prescription for RTIs. A systematic review was performed searching in the scientific databases MEDLINE PubMed and EMBASE for studies which exposed prescribers to guidelines for RTI and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Our results showed that the practitioners relied mostly on published guidelines for antibiotic prescribing, which is among the most important strategies to enhance prudent antibiotic prescribing behavior [ 49 , 50 , 51 ]. Generally, the implementation of guidelines and antimicrobial stewardship initiatives to direct prudent antibiotic prescribing are key elements in enhancing the appropriate use of antibiotics [ 41 , 44 , 49 , 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the practitioners relied mostly on published guidelines for antibiotic prescribing, which is among the most important strategies to enhance prudent antibiotic prescribing behavior [ 49 , 50 , 51 ]. Generally, the implementation of guidelines and antimicrobial stewardship initiatives to direct prudent antibiotic prescribing are key elements in enhancing the appropriate use of antibiotics [ 41 , 44 , 49 , 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…A potentially discerning aspect in the need for IMV in critical bronchiolitis may arise from complicating bacterial pneumonias. The AAP discourages the routine use of antibiotics in this population unless there is a clear source of bacterial infection [8,36]. In intubated critical bronchiolitis patients, despite practice variations across the country, early antibiotic initiation was associated with shorter duration of mechanical ventilation and shorter hospitalizations [37].…”
Section: Discussionmentioning
confidence: 99%
“…Most RTIs are self-limited with a marginal effect for antimicrobial treatment to prevent complications. 20 Evidence indicates that antimicrobial treatment of these conditions exacerbates antimicrobial resistance amongst common bacterial strains whilst providing patients with little benefit. [21][22][23][24] It also increases healthcare costs, puts patients at risk of drug reactions and allergies and predisposes them to other complications such as Clostridium difficile infections.…”
Section: Discussionmentioning
confidence: 99%
“…Implementing and improving adherence to clinical guidelines were found to be effective in reducing prescription and the inappropriate selection of antibiotics for RTIs. 20 At a national level, it is necessary to promote antibiotic agents' optimal use by improving knowledge and setting implementation strategies that control their use. Multifaceted interventions should target capacity building of practitioners especially primary care physicians on the rational use of antibiotics, developing national clinical guidelines for the management of RTIs and other conditions with common misuse of antibiotics, increasing public awareness of antimicrobial resistance, strengthening surveillance and investing in research whilst engaging policymakers, healthcare practitioners and the public.…”
Section: Con Clus Ionmentioning
confidence: 99%